(3GdCZPjIs - (3CHj GdeYGdj YHO Gdedc Hf CHj GdYdGA, GHf RgQ GdeJWHH,J (B557 (3g` s ((3aQL Hf YeGQ s)
(3ChdgG (B:s
(3Gfj CQjO Cf CJcde aj GdCOhjI GdJj jSgd hLhOgG hdG jJYGeQ aj CcKQ GdehGWf EecGfgG PcQ GdCZPjI HMSH GdCReGf s
(3BNQgG (B:s
(3hCPgGf GdHTQ JbUQ Yf eYQaI TF EdG eG LYd Gddg aj hSYgG eYQaJg hGdMeO ddg Ydi eG CfYe hCf jLYd GHJZGA eQVGJg CYeGdfG HafGQJg s
(3Vef eLehY s
(3GfXQ agQS GdWH HQbe (B21s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B27 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs